Computational fluid dynamics (CFD) analysis for a catalytic converter design - Amirnordin, Shahrin Hisham (2009)
Design of catalytic converters involves four major components including casing, washcoat, catalyst and substrate. However, the design process is complicated as it involves various parameters. One of the problems faced by designers is obtaining the performance of catalytic converters where the substrate is made up of a large number of cells. Therefore, an effort to solve the problem using Computational Fluid Dynamics (CFD) with an alternative modeling technique is deployed. This study involved a preliminary design which employed an adapted sub-grid scale modeling as an alternative method for the analysis of substrate performance. The Pahl and Beitz's model was applied in the design process. The adapted sub-grid scale modeling was used to predict the pressure loss, select the cell shape and produce the performance chart which could show the relationship between the parameters involved. The proposed adapted sub-grid scale modelling method was found to give results within 5 % error which was better compared to the single channel method. Results also indicated the advantage of hexagonal-shaped over square-shaped cells in terms of pressure loss where the fonner showed a 43 % lower value than the latter. The Mechanical-Chemical Performance Mapping (MCPM) was finally obtained. The mapping could be used to assist in the substrate design of catalytic converters.